Nardo, Ed., Charles Darwin - Brown, Robert (Teaching History: A Journal of Methods, 2004)
The name Charles Darwin, the theory of evolution, and the related concepts of natural selection and survival of the fittest still provoke fiery debates nearly 150 years after publication of The Origin of Species in 185 9. Don Nardo 's Charles Darwin is a useful, if limited, anthology of primary and secondary sources by authors such as Desmond King-Hele, Carl Sagan, and Gertrude Himmelfarb on the origins, publication, and impact, short- and Jong-term, of Darwin's ideas. Organized in four sections, this collection provides excerpts from secondary sources on "Pre-Darwinian Theories of Life's Origins," a mixture of primary and secondary sources on "Darwin Develops and Publishes his Theory of Evolution" and "The Immediate Impact of Darwin's Origin of Species," and excerpts from secondary sources on "Modern Reevaluations and Objections to Darwin's Ideas."